I died a million times : gangster noir in midcentury America - Miklitsch, Robert, 1953- (University of Illinois Press, 2021)
"In the 1950s, the gangster movie and film noir crisscrossed to create gangster noir. Robert Miklitsch takes readers into this fascinating subgenre of films focused on crime syndicates, crooked cops, and capers. With the Senate's organized crime hearings and the brighter-than-bright myth of the American Dream as a backdrop, Miklitsch examines the style and history, and the production and cultural politics, of classic pictures from The Big Heat and The Asphalt Jungle to lesser-known gems like 711 Ocean Drive and post-Fifties movies like Ocean's Eleven. Miklitsch pays particular attention to trademark leitmotifs including the individual versus the collective; the family as a locus of dissension and rapport; the real-world roots of the heist picture; and the syndicate as an octopus with its tentacles deep into law enforcement, corporate America, and government. If the memes of gangster noir remain prototypically dark, the look of the films becomes lighter and flatter, reflecting the influence of television and the realization that, under the cover of respectability, crime had moved from the underworld into the mainstream of contemporary everyday life"--